A bio-inspired hybrid nanosack for graft vascularization at the omentum. (1st September 2016) - Hwang, Patrick T.J.; Lim, Dong-Jin; Fee, Timothy; Alexander, Grant C.; Tambralli, Ajay; Andukuri, Adinarayana; Tian, Liqun; Cui, Wanxing; Berry, Joel; Gilbert, Shawn R.; Jun, Ho-Wook
Graphical abstract: Abstract: For three-dimensional tissue engineering scaffolds, the major challenges of hydrogels are poor mechanical integrity and difficulty in handling during implantation. In contrast, electrospun scaffolds provide tunable mechanical properties and high porosity; but, are limited in cell encapsulation. To overcome these limitations, we developed a "hybrid nanosack" by combination of a peptide amphiphile (PA) nanomatrix gel and an electrospun poly (ε-caprolactone) (ePCL) nanofiber sheet with porous crater-like structures. This hybrid nanosack design synergistically possessed the characteristics of both approaches. In this study, the hybrid nanosack was applied to enhance local angiogenesis in the omentum, which is required of tissue engineering scaffolds for graft survival. The ePCL sheet with porous crater-like structures improved cell and blood vessel penetration through the hybrid nanosack. The hybrid nanosack also provided multi-stage fibroblast growth factor-2 (FGF-2) release kinetics for stimulating local angiogenesis. The hybrid nanosack was implanted into rat omentum for 14 days and vascularization was analyzed by micro-CT and immunohistochemistry; the data clearly demonstrated that both FGF-2 delivery and porous crater-like structures work synergistically to enhance blood vessel formation within the hybrid nanosack. Therefore, the hybrid nanosack will provide a new strategy for engineering scaffolds to achieve graft survival in the omentum by stimulating local vascularization, thus overcoming the limitations of current strategies. Statement of Significance: For three-dimensional tissue engineering scaffolds, the major challenges of hydrogels are poor mechanical integrity and difficulty in handling during implantation. In contrast, electrospun scaffolds provide tunable mechanical properties and high porosity; but, are limited in cell encapsulation. To overcome these limitations, we developed a "hybrid nanosack" by combination of a peptide amphiphile (PA) nanomatrix gel and an electrospun poly (ε-caprolactone) (ePCL) nanofiber sheet with porous crater-like structures. This design synergistically possessed the characteristics of both approaches. In this study, the hybrid nanosack was applied to enhance local angiogenesis in the omentum, which is required of tissue engineering scaffolds for graft survival. The hybrid nanosack was implanted into rat omentum for 14 days and vascularization was analyzed by micro-CT and immunohistochemistry. We demonstrate that both FGF-2 delivery and porous crater-like structures work synergistically to enhance blood vessel formation within the hybrid nanosack. Therefore, the hybrid nanosack will provide a new strategy for engineering scaffolds to achieve graft survival in the omentum by stimulating local vascularization, thus overcoming the limitations of current strategies.